Peranan geokimia terhadap stabilitas lereng tanah residu volkanik di daerah Panti Jember Jawa Timur - , Amien Widodo, Ir.,M.Si.; , Prof. Ir. Sukandarrumidi, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Research the causes of landslide occurrence with the number of lots that occur together in one place is still a bit done. We propose that the initial cause of landslide is due to the high weathering process of the Old Quaternary volcanic rocks. The goal of this research is to assess the geochemical characteristics of the material terms of slope and slope stability. This research is important because in Indonesia the Old Quaternary volcanic soil residues are huge numbers, scattered in various places and become dense settlement. The research location is situated on the southern slopes Mt.Argopuro at. Panti Subdistrict of Jember Regency East Java. This location was chosen because of number of lots landslides occur simultaneously. Materials used in this study are the maps, reports, satellite images, topographic measurements, test results of SPT, DCPT, field permeability tests and soil samples will be checked for physical properties, chemical and organic content. Results of analysis of all data expected to note that the failure surface is a zone of geochemical anomalies. Anomaly is a situation where there is enrichment or impoverishment of geochemical elements, thus affecting the shear strength of soil. The results showed that the soil in the study area can be divided into 3 layers of soil residue, layers and layers of rock being weathered bedrock breccia Argopuro. Residual soil layer has a value between 1-9 SPT blows/feet and conical value <30 kg/cm2 categorized as very soft and thick soil about 16 meters, while the weathered rock layer at 16-20 meters depth is characterized by the value of SPT 4-20 blows/feet and conus value > 250 kg/cm2. Bedrock layers at depths > 20 meters with SPT> 60 blows/feet. Field permeability indicates that the soil on the surface to a depth of - 1.0 and - 2.0 m were impermeable due to permeability rates between 1.33 x 10-5 - 9.50 x 10-5 cm / sec. The distribution of clay particle size was increasing percent weight > 50%. Anomalies SiO2 / (Al2O3 + Fe2O3) (ratio of silica-sesquoside) at a depth of 9 meters. Chemical Index of Alteration (CIA)> 90% is the residual soil and combined with ACNK (Al2O3- (CaO + Na2O)-K2O) diagram shows that the soil residue in the dominance of kaolin clay group. Chemical Weathering Index (CWI), about 60% showed residual soil. Results of analysis of organic material indicates that in almost every depth of soil containing organic material. Mineral haloisit dominate almost every depth indicate an anomaly because it is based on the formation must have existed on the surface. Argopuro Breccia matrixs have been changed by hydrothermal alteration process. The safety factor (SF) shows the landslide area is located at a depth of 9-12 meters. It can be concluded that the geochemical processes that occur in the cracks along the plane of shear strength has been weakened through the process of translocation of the elements of soil cement materials such as silica, alumina, iron oxides and organic materials as well as the migration of grains and clay minerals. Volcanic residual soil at Panti Jember on the slopes of Mt Argopuro in critical condition.